Analyzing Forest and Land Fire Disaster Prevention Programs in Riau, Indonesia - Ahmad Fadhillah; Moses Glorino Rumambo Pandin; Toetik Koesbardiati (Qubahan Academic Journal)
In Indonesia, forest and land fires are natural disasters that often occur every year, especially during the dry season. To overcome this, the government, non-governmental organizations, business actors and the community are carrying out programs to handle a paradigm shift in the disaster management model from responsive to more preventive in order to reduce it by emphasizing disaster risk reduction efforts and active involvement. The aim of this research is to examine government, company and non-governmental organization intervention programs related to preventing forest and land fire disasters. Qualitative research methods are used to explore sources of information in answering research questions. Data collection uses open interviews and observations as well as Forum Group Discussions regarding strategic intervention designs carried out by local governments, non-governmental organizations, and local communities. The research results show that the forest and land fire prevention model require a sustainable intervention program. The intervention carried out by the provincial government and local government involves all elements of society, including entrepreneurs, non-governmental organizations, fire care communities, farmer groups and the community itself. The results achieved within three years were a reduction in the incidence of forest and land fires.